2020
DOI: 10.1103/physrevmaterials.4.043401
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of phase-pure rhombohedral HfZrO4 in pulsed laser deposited thin films

Abstract: Controlling the crystalline structure of Hafnium Zirconate and its epitaxial relationship to a semiconducting electrode has a high technological interest, as ferroelectric materials are key ingredients for emerging electronic devices. Using Pulsed Laser Deposition, a phase pure, ultrathin film of Hf0.5Zr0.5O2 is grown epitaxially on a GaN (0001) / Si (111) template. Since standard microscopy techniques do not allow to determine with certitude the crystalline structure of the film due to the weak scattering of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 45 publications
3
43
1
Order By: Relevance
“…Phase analysis by means of 2h scans around poles corresponding to a representative domain (Figure 8(c,d)) reveals 3:1 multiplicity, pertaining to an r-phase, on both these substrates. HAADF-STEM images reported by Lours et al [47] clearly show these domains and the coherent domain boundaries on the GaN-buffered Si substrate (Figure 8(e)). The HAADF-STEM image from just one domain (Figure 8 sectional lamella.…”
Section: Hzo On Hexagonal and Trigonal Substrates: Polar R-phasementioning
confidence: 57%
See 2 more Smart Citations
“…Phase analysis by means of 2h scans around poles corresponding to a representative domain (Figure 8(c,d)) reveals 3:1 multiplicity, pertaining to an r-phase, on both these substrates. HAADF-STEM images reported by Lours et al [47] clearly show these domains and the coherent domain boundaries on the GaN-buffered Si substrate (Figure 8(e)). The HAADF-STEM image from just one domain (Figure 8 sectional lamella.…”
Section: Hzo On Hexagonal and Trigonal Substrates: Polar R-phasementioning
confidence: 57%
“…Next, we grew 6 nm thick HZO layers on substrates that, by virtue of their symmetry, impose (111) orientation to the film. In this pursuit, we used (0001) hexagonal substrates such as GaN buffered Si [47] with a 1 ¼a 2 ¼3.23 Å, a ¼ 120 and sapphire with a 1 ¼a 2 ¼3.46 Å, a ¼ 120 , both of which provide an initial compressive strain to the {111} plane of HZO (a 1 , a 2 $ 3.56-3.62 Å, a $ 120 depending on the polymorph). The {111} pole figures on both these substrates (Figure 8(a,b)) clearly show that these films are (111) oriented.…”
Section: Hzo On Hexagonal and Trigonal Substrates: Polar R-phasementioning
confidence: 99%
See 1 more Smart Citation
“…Further experiments confirmed that YHO films grown on (001) YSZ contain four types of orientations: o 1 , o 2 , o 3 , o 4 , whereas films grown on (100) ITO/(100) YSZ contain two types of orientations: o 5 and o 6 . [74] In addition, Yoong et al [56] studied the growth of epitaxial HZO thin films on [74] 700 0.013 9 --YHO/(001)ITO/(001)YSZ [74] YHO/(110)ITO/(110)YSZ [34] 700 0.013 15 16 Yes YHO/(ITO)/(111)YSZ [136] 700 0.013 14 10 -YHO/YSZ [50] 700 0.013 20 --HZO/(0001)GaN/(111)Si [76] 750 0.1 5.83 --YHO/ITO/YSZ [33,35,137] a) 0.013 10-115 25 No YHO/YSZ/(001)Si [77] 700 0.2 20 -HZO/TiN/(001)YSZ [138] 700 2.6*10 À8 15 7-30 -HZO/TiN/(011)YSZ [138] HZO/TiN/(111)YSZ [138] HZO/LSMO/(001)LAO [56] 550 0.13 10 20 Yes…”
Section: Substrate And/or Bottom Electrode Selectionmentioning
confidence: 99%
“…5 Epitaxial films are being investigated now very actively. Several conducting or semiconducting substrates or templates, including Si wafers, 6 TiN, 7 GaN, 8 and indium tin oxide, 9 have been used to deposit epitaxial films of ferroelectric doped HfO 2 . In contrast, epitaxy of hafnia on perovskite-type oxide electrodes has only been reported on Nb-doped SrTiO 3 (Nb:STO) 10 and La 0.67 Sr 0.33 MnO 3 (LSMO).…”
Section: Introductionmentioning
confidence: 99%